From hospital to home: A heightened window of vulnerability post-critical illness - Amanda Fuchsia Howard; Kelsey Lynch; Sally Thorne; Leanne M. Currie; Rakesh C. Arora; Robert C. McDermid; Omar Ahmad; Sarah Crowe; Sybil Hoiss; Anita David; Joanne Chu; Alice Erchov; et al. (PLoS ONE, 2025)
Background Healthcare innovations have not kept pace with the burden of critical illness survivorship. The majority of patients treated in an intensive care unit (ICU) will survive but suffer new or worsening physical, cognitive or mental health sequelae, known as post-intensive care syndrome (PICS). For these survivors, the transition from hospital-based acute care to community-based care is often complex, with high rates of emergency department visits and unplanned hospital readmission. The purpose of this analysis is to describe ICU survivor and family caregiver experiences navigating the challenges in the transition from hospital to home. Methods In this qualitative interpretive description study, data from semi-structured interviews with ICU survivors and family caregivers in the months following discharge from the hospital to home were analyzed using thematic and constant comparative methods. Results The 47 study participants included 28 survivors (mean age 58, 17 men and 11 women) and 19 family caregivers (mean age 53, 6 men and 13 women), who represented 32 cases. The challenges experienced when transitioning from hospital included (1) feeling too ill to go home and pushed out of the hospital without a plan, (2) confronting illness and exhaustion without a safety net, and (3) managing at home with inadequate healthcare. During this time, patients were vulnerable to stagnation or deterioration of their mental and physical health, unmet healthcare needs, and unplanned emergency department visits and rehospitalization. Conclusions The challenging transition from the hospital setting suggests a heightened window of vulnerability in the initial months post-discharge and emphasizes a crucial missing middle in our healthcare system, leaving vulnerable patients at risk for ongoing and new health problems.